Pelatihan Komunikasi Positif dan Penguatan Kepercayaan Diri bagi Siswa Sekolah Dasar di SDN Antasan Besar 7 Banjarmasin - Ratih Pranawa Widagda; Rizky Nazzara; Sabrina Tsalsadifa; Triana Ayu Wulandari; Zuliana Agustin; Sudirwo Sudirwo; Anna Nur Faidah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service activity aims to improve positive communication skills and foster self-confidence in students at Antasan Besar 7 Elementary School, Banjarmasin. The background to this activity is the results of observations showing that some students still have low communication skills and lack of self-confidence, characterized by shyness, nervousness, and reluctance to speak in public. The training was conducted by students of Lambung Mangkurat University on September 17, 2025, involving 16 fifth-grade students. The implementation method included preparation, interactive training, role-playing, speaking simulations in front of the class, and evaluation through pre-post observation and questionnaires. The training materials included understanding positive communication, the use of polite language, emotional control, eye contact, and facial expressions, as well as self-confidence-building exercises through the activities "Dare to Speak" and "Introduce Myself". The evaluation results showed an increase in students' average scores in the aspects of participation, positive attitudes, and courage to speak in front of the class after participating in the training. This activity has proven effective in helping students develop interpersonal communication skills and strengthen self-confidence, as well as having a positive impact on a more supportive learning atmosphere in the elementary school environment.